Neomassaria khayae sp. nov., a novel pleosporalean species on Khaya senegalensis from Guangdong Province, China - Yang, Yunhui; Liao, Chunfang; Manawasinghe, Ishara S.; Roberto Gomes De Farias, Antonio; Dong, Zhangyong (Phytotaxa, 2023)
Khaya senegalensis is a tropical plant native to Africa and grown as an ornamental plant in Southern China. During our sample collection in Guangdong Province, China, a saprobic Dothideomycetes was collected from a dead stem of K. senegalensis. The collection was identified as a neomassaria-like species based on the morphology. For further identification of the species, multigene phylogenetic analyses were conducted using large subunit nrDNA (LSU), small subunit nrDNA (SSU), RNA polymerase II second largest subunit gene (rpb2) and translation elongation factor 1-alpha (tef1-α). Based on morphology and phylogeny we identified our collection as a new species and introduced it as Neomassaria khayae. Morphologically, N. khayae distinguishes from other closely related species in terms of larger ascomata, asci and ascospore. In addition, this is the first report of Neomassaria species on K. senegalensis in China. This study will add to the biodiversity of saprobic fungi associated with Meliaceae hosts in Southern China.